A retrospective analysis of post‐transplant lymphoproliferative disorder following liver transplantation. (4th December 2017) - Fararjeh, Feras Al; Mahmood, Shameem; Tachtatzis, Phaedra; Yallop, Deborah; Devereux, Stephen; Patten, Piers; Agrawal, Kosh; Suddle, Abid; O'Grady, John; Heaton, Nigel; Marcus, Robert; Kassam, Shireen
Abstract: Objective: To evaluate response rates and survival in adults developing post‐transplant lymphoproliferative disorder (PTLD) following liver transplantation. Methods: Patients were identified retrospectively and data collected through local liver and haematology electronic databases and pharmacy records. Results: Forty‐five patients were identified. The median age at first transplant and at development of PTLD was 48 and 54 years, respectively, with the median time from transplant to PTLD diagnosis of 56 months. The majority of cases (76%) were monomorphic B‐cell lymphomas, and 36% of tumours were EBV positive. Treatment involved reduction in immune‐suppression (RIS) in 30 (67%) with RIS the only treatment in 3. Ten (22%) patients were treated with rituximab alone, 13 (29%) with chemotherapy alone and 14 (31%) patients were treated with rituximab and chemotherapy. Twenty‐six (58%) patients achieved a complete response (CR). At a median follow‐up of 27 months, the median overall survival (OS) was 50 months. Response and OS were not associated with clinical factors or the use of rituximab. Conclusion: Outcomes reported in this study are favourable and comparable to those reported previously. The addition of rituximab did not appear to have improved outcomes in this series, although a significant proportion of patients were able to avoid chemotherapy.